Establishment of Pancasila Student Profile Through the Physical Education Process of The Independent Curriculum - Wildani Ali Putra; Indra Safari; Adang Sudrazat (Universitas PGRI Palembang, 2023)
Character education is a serious and systematic effort from the government, one of the steps in maximizing the character education program is the pancasila student profile program, This research aims to find out how the process of forming a pancasila student profile through physical education learning with an independent curriculum at SMK, this research examines how programs, implementation, and obstacles in forming a pancasila learning profile through learning physical education with an independent curriculum, this research uses qualitative descriptive methods by conducting observations, interviews and documentation so that it can form a framework for the formation of a pancasila student profile through a reviewer, the result of this research is that in physical education almost all dimensions of the pancasila student profile can be developed such as through habituation of prayer before and after learning, interacting directly in learning, helping each other and working together, looking for material information independently, daring to ask questions and express opinions, and carrying out motion tasks with different approaches, programs from schools such as workshops on pancasila student profiles are carried out to maximize achievement and understanding of pancasila student profiles, intracurricular, collegicular and extra-curricular activities are required to always apply the dimensions of the pancasila student profile to make habituation of values Pancasila through school culture, the effects of the pandemic causing students to become less familiar with school discipline make it a new challenge in implementing the Pancasila student profile.